2005
DOI: 10.1111/j.1460-9568.2005.04179.x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interactions between oscillatory activities of different frequencies in the subthalamic region of patients with Parkinson's disease

Abstract: Synchronization of neuronal activity evident in the local field potential (LFP) recorded in the subthalamic region of patients with Parkinson's disease occurs at low frequencies (< 30 Hz) and, in some patients following treatment with levodopa, at high frequencies between 65 and 85 Hz. Here we investigate the functional relationship between these different activities by determining whether spontaneous fluctuations in their strength are correlated across time. To this end, we analysed recordings of LFPs from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 45 publications
9
51
2
Order By: Relevance
“…A surprising finding contradicting previous reports was the fail- ure to demonstrate a change in power in the STN LFP because of drug state. This suggests that the effects of levodopa challenges might have been suboptimal compared with previous studies in which a suppression of ␤ band LFP power (Priori et al, 2004;Alonso-Frech et al, 2006;Kühn et al, 2006b) and an increase in ␥ band LFP power (Williams et al, 2002;Alegre et al, 2005;Fogelson et al, 2005;Alonso-Frech et al, 2006;Devos and Defebvre, 2006) have been reported. LFP recordings were consistently performed on the fifth day postoperatively, and it is possible that levodopa effects were attenuated by microlesional effects, especially postoperative edema, at this time.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…A surprising finding contradicting previous reports was the fail- ure to demonstrate a change in power in the STN LFP because of drug state. This suggests that the effects of levodopa challenges might have been suboptimal compared with previous studies in which a suppression of ␤ band LFP power (Priori et al, 2004;Alonso-Frech et al, 2006;Kühn et al, 2006b) and an increase in ␥ band LFP power (Williams et al, 2002;Alegre et al, 2005;Fogelson et al, 2005;Alonso-Frech et al, 2006;Devos and Defebvre, 2006) have been reported. LFP recordings were consistently performed on the fifth day postoperatively, and it is possible that levodopa effects were attenuated by microlesional effects, especially postoperative edema, at this time.…”
Section: Discussioncontrasting
confidence: 41%
“…Log power and transformed dCoh data were averaged across three different frequency bands: sub-␤ (3-13 Hz), ␤ (14 -35 Hz), and ␥ (65-90 Hz). These discontinuous frequency bands were selected because several previous studies have shown that spectral peaks and physiologically reactive LFP power in the STN are seen below 35 Hz and again from ϳ65-90 Hz Williams et al, 2002;Priori et al, 2004;Alegre et al, 2005;Fogelson et al, 2005;Alonso-Frech et al, 2006;Devos and Defebvre, 2006;Kühn et al, 2006a,b;Androulidakis et al, 2007). The precise frequency range of the ␤ band was chosen to match (as far as possible, given differences in sampling rates) the band determined to be focally generated in the STN in recent intraoperative Chen et al, 2006) and postoperative (Kühn et al, 2006a) recordings.…”
Section: Methodsmentioning
confidence: 99%
“…Tremor-related oscillations, although common in single-unit recordings (Hutchison et al 1997;Levy et al 2000Levy et al , 2002a are not a consistent or strong feature in LFP signals, probably due to the variable phase relationships between neurons oscillating at tremor frequencies (Hurtado et al 1999(Hurtado et al , 2005Levy et al 2000). Instead oscillatory field potential activity in PD patients off medications is particularly prominent in the beta band (Brown et al 2001;Kuhn et al 2005;Levy et al 2002a;Weinberger et al 2006) and, to a lesser extent, in the gamma band (35-90 Hz) (Fogelson et al 2005;Pogosyan et al 2006;Trottenberg et al 2006). In contrast to the beta activity, gamma band oscillations in the basal ganglia have been hypothesized to play a prokinetic role and to contribute to movement generation (Brown 2003;Brown and Williams 2005), as these oscillations are increased during movement and by treatment with dopaminergic medications, in tandem with clinical improvement (AlonsoFrech et al 2006;Androulidakis et al 2007;Cassidy et al 2002;Williams et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To analyze such temporal relationships, we used a correlation matrix approach (Fig. 3 F, G), which has been previously used to reveal interfrequency relationships in corticobasal ganglia networks (Masimore et al, 2004;Fogelson et al, 2005). The correlation matrix uncovers two pieces of information.…”
Section: Detection Of Low-threshold Spike Bursts Allows Separation Ofmentioning
confidence: 99%
“…To investigate the fundamental frequencies in the ECoG and LFP data, we used the correlation matrix method previously described by Masimore et al (2004) that has successfully been applied to basal ganglia LFP data (Fogelson et al, 2005;Masimore et al, 2005). Briefly, power spectral parameters were calculated in short time windows (10 s/5 s overlap or 12 s/6 s overlap).…”
Section: Introductionmentioning
confidence: 99%